Urban transport and growth management strategies: A tale of two southeast asian cities at the dawn of the new millennium - Jamilah Mohamad, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2005)
Over the last two decades, many Southeast Asian cities underwent unprecedented growth that has led to the degradation of their urban traffic situations. Increases in the ownership and use of motor vehicles led to massive road building programmes adding on to the resultant deterioration in the quality of life within major capital cities. Based on official transport studies which have been completed for both Kuala Lumpur and Manila, this paper aims to compare urban transport characteristics, land use disposition and policies advocated in both Metro Manila and Kuala Lumpur. It is found that both cities attempt to manage their liveability challenge by implementing a public transportation system (the LRT) that could help satisfy increased travel demand and alleviate transport congestion in the cities, and by seeking to develop areas outside the city centres so that they will decrease the need to obtain employment and other urban services in the city centres. The goal of easing traffic congestion by enhancing the public transport modes has not been very successful because of the strong, non-rational value attached to private car ownership. The paper concludes that attitudinal rather than physical change is the real challenge to the management of liveability in the two Southeast Asian Cities